Genetic modification of glaucoma associated phenotypes between AKXD-28/Ty and DBA/2J mice - Anderson, Michael G (BioMed Central, 2001)
BACKGROUND: Glaucoma is a common disease but its molecular etiology is poorly understood. It involves retinal ganglion cell death and optic nerve damage that is often associated with elevated intraocular pressure. Identifying genes that modify glaucoma associated phenotypes is likely to provide insights to mechanisms of glaucoma. We previously reported glaucoma in DBA/2J mice caused by recessive alleles at two loci, isa and ipd, that cause iris stromal atrophy and iris pigment dispersion, respectively. A approach for identifying modifier genes is to study the effects of specific mutations in different mouse strains. When the phenotypic effect of a mutation is modified upon its introduction into a new strain, crosses between the parental strains can be used to identify modifier genes. The purpose of this study was to determine if the effects of the DBA/2J derived isa and ipd loci are modified in strain AKXD-28/Ty. RESULTS: AKXD-28/Ty mice develop glaucoma characterized by intraocular pressure elevation, retinal ganglion loss, and optic nerve excavation. In AKXD-28/Ty, isa causes an iris stromal atrophy phenotype as in DBA/2J. However, the iris pigment dispersion phenotype associated with ipd in DBA/2J does not occur in AKXD-28/Ty. Additionally, a greater severity and speed of retinal and optic nerve damage following intraocular pressure elevation in AKXD-28/Ty compared to DBA/2J mice suggests that AKXD-28/Ty is more susceptible to pressure-induced cell death. CONCLUSIONS: The consequences of the ipd and isa mutations are modified in the AKXD-28/Ty background. These strains provide a resource for the identification of modifier genes that modulate pigment dispersion and susceptibility to pressure-induced cell death.